Textbook of biochemistry : with clinical correlations - 4 0 16; Devlin, Thomas M.; 5 (Hoboken, NJ : John Wiley & Sons, 2011)
This book presents a clear and precise discussion of the biochemistry of eukaryotic cells, particularly those of mammalian tissues, relates biochemical events at a cellular level to the subsequent physiological processes in the whole animal, and cites examples of abnormal biochemical processes in human disease. The organization and content are tied together to provide students with the complete picture of biochemistry and how it relates to human diseases--Provided by publisher.
Part I: Structure of macromolecules -- 1. Eukaryotic Cell Structure -- 2. DNA and RNA: Composition and Structure -- 3. Proteins I: Composition and Structure -- Part II: Transmission of information -- 4. DNA Replication, Recombination, and Repair -- 5. RNA: Transcription and RNA Processing -- 6. Protein Synthesis: Translation and Posttranslational Modifications -- 7. Recombinant DNA and Biotechnology -- 8. Regulation of Gene Expression -- Part III: Functions of proteins -- 9. Proteins II: Structure-Function Relationships in Protein Families -- 10. Enzymes: Classification, Kinetics, and Control -- 11. The Cytochromes P450 and Nitric Oxide Synthases -- 12. Biological Membranes: Structure, Receptors, and Solute Transport -- 13. Fundamentals of Signal Transduction -- Part IV: Metabolic pathways and their control -- 14. Bioenergetics, Mitochondria, and Oxidative Metabolism -- 15. Carbohydrate Metabolism I: Major Metabolic Pathways and Their Control -- 16. Carbohydrate Metabolism II: Special Pathways and Glycoconjugates -- 17. Lipid Metabolism I: Synthesis, Storage, and Utilization of Fatty Acids and Triacylglycerols -- 18. Lipid Metabolism II: Pathways of Metabolism of Special Lipids -- 19. Amino Acid and Heme Metabolism -- 20. Purine and Pyrimidine Nucleotide Metabolism -- 21. Metabolic Interrelationships -- 22. Biochemistry of Hormones -- Part V: Physiological processes -- 23. Molecular Cell Biology -- 24. Cell Cycle, Programmed Cell Death, and Cancer -- 25. Digestion and Absorption of Basic Nutritional Constituents -- 26. Vitamins and Minerals: Requirements and Function -- 27. Macronutrients: Metabolic Effects and Health Implications -- Appendix: Review of Organic Chemistry -- Glossary -- Index.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Biochemistry.;Clinical biochemistry.;Biochemical Phenomena. -- 20; 20; 2